Challenging the myth of inclusivity in Special Economic Zones: unveiling equity gaps in local economic development in South Africa - Muringa, Tigere Paidamoyo; Shava, Elvin; Oladejo, Olufemi Michael (Frontiers in Sustainable Cities, 2025)
IntroductionSpecial Economic Zones (SEZs) are often praised as socially cohesive and inclusive economic development engines. However, this study argues that such assumptions overlook critical equity gaps.MethodsThe study analyzed data from 36 semi-structured interviews conducted across 10 South African municipalities. Two empirical questions guide this inquiry: What systemic barriers within SEZs' policy and operational frameworks hinder their ability to address the needs of marginalized populations and communities? How can targeted policy measures and stakeholder engagement mechanisms be designed and implemented to ensure SEZs promote sustainable and equitable local economic development?ResultsFindings reveal that SEZs have succeeded in creating jobs and improving infrastructure, but fail to adequately address the needs of local communities. Despite their potential, SEZs cannot inherently foster inclusivity without deliberate policy measures and robust stakeholder engagement. Key barriers include uneven distribution of resources, weak enforcement of inclusive policies, and inadequate community engagement.DiscussionThis study challenges the argument that SEZs inherently benefit local communities and that they risk perpetuating inequalities unless designed with equity at the forefront. Policymakers must implement targeted interventions, including transparent frameworks and participatory mechanisms, to ensure SEZs deliver equitable outcomes. By demystifying the perceived inclusivity of SEZs, this research highlights the critical need to rethink their implementation to promote sustainable and equitable development.